The symbol and the banquet: A prolegomena to a future metaphysics of Nicaea - Delport, Khegan M. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
Contemporary research on ‘the Arian Crisis’ has undermined earlier polemical readings of Arius as simply a heresiarch, or a comic-book villain, within the debate leading up to and beyond Nicaea. Historical scholarship demonstrates a more sophisticated picture of Arius as an Alexandrian theologian who imbibed the metaphysical and logical traditions of his time, growing out of a broadly conservative and Platonic ferment. The available evidence suggests a figure attuned to the problems of metaphysical terminology when applied to the divine nature, especially as regards the relation of God to created being, demonstrating an ‘orthodox’ theology of divine transcendence. And yet, in the wake of Arius, pro-Nicene theologians adopted the controversial terminology of the homoousia to make sense of the incarnation, that is, of the genuine communication of the divine nature in and through the Son. It implied the adoption of a novel metaphysics to articulate the radical nature of this divine communication. This article argues that thinking through the metaphysical implications of Nicaea today means a continuation of this gesture: a non-identical repetition and radicalisation of Nicene orthodoxy. It suggests that an ongoing, fallibilist explication of theology through metaphysical concepts is, in some sense, legitimised through the incarnation, insofar as God is truly communicated into created forms while always being transcendent to them. The article argues that new continuities within Christian orthodoxy can be made and reimagined through ruptures within the tradition, and that this appears to be in line with the eschatological and apophatic trajectory of orthodoxy itself. Contribution: The article attempts to expound the element of metaphysical innovation found within the Nicene tradition, and thereby to outline what this may mean for a Christian theology of tradition.